Preventive Strategies For Mother And Child Health Through Unani System Of Medicine- A Literary Research - Akhtar, Shamim; Karim, Md. Shafat; Alam, Md. Tanwir (Journal of Neonatal Surgery, 2025)
Introduction: Maternal and child health (MCH) has long been an issue of paramount importance on a worldwide scale. A global maternal death rate of less than 70 per 100,000 live births by 2030 was set as an objective by the Sustainable Development Goals (SDGs). Significant advancements have been made in the field of MCH until now. Despite India's efforts to reduce maternal mortality rates (MMR), significant challenges remain, reflecting the vulnerability of pregnant women, infants, and children under 5 years of age to infections and diseases. It is necessary to explore the suggestions and guidelines for pregnancy, the pregnant mother, and the child through USM. Aims and Objectives: This study is set to collect and compile all the measures advocated for mother and child care mentioned in classical Unani literature. Methodology: Related Unani literature was searched in classical textbooks, manuscripts, journals, and printed materials. Various search engines like Google Scholar, PubMed, Medline, etc., with relevant Unani terminologies like ‘mother and child care in Unani,’ ‘ANC Care in Unani,’ etc., were explored. Observation and Finding: Unani classical literature has revealed a complete description of the prevention of maternal and child health. Food supplements and different regimens, as well as drugs for newborns and pregnant mothers, have been indicated. Conclusion: The Approach of Unani medicine is valuable for MCH, emphasizing preventive care, nutrition, and traditional practices. By integrating Unani principles with modern healthcare, we can promote the well-being of mothers and children, aiming for lifelong health and development.